Electron paramagnetic resonance enhanced crystal field analysis for low point-group symmetry systems: C2v sites in Sm3+:CaF2/SrF2. (30th November 2018) - Horvath, S P; Wells, J-P R; Reid, M F; Yamaga, M; Honda, M
Abstract: We present a comprehensive spectroscopic study of C point-group symmetry sites in Sm :CaF /SrF codoped with either NaF or LiF. Data includes electron paramagnetic resonance measurements of Zeeman and hyperfine interactions for the ground state, as well as site-selective excitation and fluorescence spectroscopy up to the G multiplet. Inclusion of the EPR data allowed us to determine unique crystal-field parameters. The parameters provide information about the geometry of the sites and the nature of the interactions between the Sm dopant and the alkaline earth co-dopant.